CONSTRUCTION OF ISLAMIC LAW AND CUSTOMARY LAW IN JAVANESE TONDANO SOCIETY - Rohmatul Faizah (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
Kampung Jawa Tondano is located in the center where the majority of the population is Christian. For hundreds of years, the people of Jaton Village have lived side by side with the majority of Minahasa tribes which have different religions. Long historical factors make Jaton Village unique. This is because the residents of Jaton Village are direct descendants of Kyai Modjo, who was a religious teacher from Prince Diponogoro who was banished by the Dutch colonialists along with his 63 followers to the Tondano area in 1828.This research aimed to observe the form of Islamic legal construction and the customary law of the Jaton community. whether there is a correlation or contradiction. This study will answer questions about what forms of construction of Islamic law and customary law in the Javanese Tondano community. The method used is qualitative with a case study approach through observation and in-depth interviews. The results showed that the construction of Islamic law and the customary law of the Javanese Tondano people were related and not contradictory. The Jaton community also still adhered to their ancestral culture from Java and uphold the norms of Islamic teachings which are a legacy from their ancestors.